2016
DOI: 10.1186/s12284-016-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Mapping of Cold Tolerance Genes at the Seedling Stage in Rice

Abstract: BackgroundRice is a temperature-sensitive crop and its production is severely affected by low temperature in temperate and sub-tropical regions. To understand the genetic basis of cold tolerance in rice, we evaluated the cold tolerance at the seedling stage (CTS) of 295 rice cultivars in the rice diversity panel 1 (RDP1), these cultivars were collected from 82 countries.ResultsThe evaluations revealed that both temperate and tropical japonica rice cultivars are more tolerant to cold stress than indica and AUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 35 publications
6
72
0
Order By: Relevance
“…We found several peaks located within or near previously reported QTLs (Table 3; S4 Table) including 11 in ALL ( qCTB1 and COLD3 , L21, qCTS4-1 , qCTS4-2 , qCTS7 , qCTS7-2 , qCTF8 , qCTS8-3 , qCTS1-5 , qCTS7-2 , and qCTF12 ), eight in INDICA (L21, L46, L107, qCST10 , qCTF12 , qCTS11-5 , qCTS6-2 and qCTS4-3 ), eight in JAPONICA [L8, L48, qLTG-4 , qCTS4-1 , qCTS4-2 , qCTS6-1 , COLD4 and qCTS7(2) ], four in temperate japonica [ qCTS4-1 , qCTS4-2 , qCTS1-5 , and qCTS11(2)-2 ] and 10 in tropical japonica ( qCTS5 , qCTS10 , L51, qLTG-5-2 , qCTS5 , L72, qPSST-7 , qCTS7 , L79, L102, and qLTG-10 ). The QTLs, qCTS4-1 , qCTS4-2 , COLD4 , qCTB5 and qCTS7(-2) were identified in JAPONICA which is in agreement with our study [1, 6, 13, 32, 4449]. Moreover, qCTS4-1 and qCTS4-2 are two major QTLs that were observed in ALL , JAPONICA and temperate japonica; another major QTL, CTB7-2 , was detected in both JAPONICA and ALL ; and finally a QTL, qCTF12 was observed in both INDICA and ALL .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found several peaks located within or near previously reported QTLs (Table 3; S4 Table) including 11 in ALL ( qCTB1 and COLD3 , L21, qCTS4-1 , qCTS4-2 , qCTS7 , qCTS7-2 , qCTF8 , qCTS8-3 , qCTS1-5 , qCTS7-2 , and qCTF12 ), eight in INDICA (L21, L46, L107, qCST10 , qCTF12 , qCTS11-5 , qCTS6-2 and qCTS4-3 ), eight in JAPONICA [L8, L48, qLTG-4 , qCTS4-1 , qCTS4-2 , qCTS6-1 , COLD4 and qCTS7(2) ], four in temperate japonica [ qCTS4-1 , qCTS4-2 , qCTS1-5 , and qCTS11(2)-2 ] and 10 in tropical japonica ( qCTS5 , qCTS10 , L51, qLTG-5-2 , qCTS5 , L72, qPSST-7 , qCTS7 , L79, L102, and qLTG-10 ). The QTLs, qCTS4-1 , qCTS4-2 , COLD4 , qCTB5 and qCTS7(-2) were identified in JAPONICA which is in agreement with our study [1, 6, 13, 32, 4449]. Moreover, qCTS4-1 and qCTS4-2 are two major QTLs that were observed in ALL , JAPONICA and temperate japonica; another major QTL, CTB7-2 , was detected in both JAPONICA and ALL ; and finally a QTL, qCTF12 was observed in both INDICA and ALL .…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al [32] evaluated 295 RDP1 accessions genotyped with 36,901 high quality SNPs for cold tolerance at the seeding stage. Subsequent, GWA mapping identified 67 QTL located on 11 chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al (2016) detected 132 QTL for nature chilling and cold-shock tolerance at the seedling stage by a GWAS analysis of 527 rice cultivars. Wang et al (2016) identified 67 QTLs for cold tolerance at the seedling stage, and 56 of these QTLs were located in regions that had not been reported to contain cold tolerance-related QTLs. Shakiba et al (2017) identified 42 QTLs associated with cold tolerance at the seedling stage, 20 of which did not co-localize with previously reported cold-tolerant QTLs.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of global warming means that crop plants, including rice, will be more exposed to extreme growing environments, e.g., low and high temperatures. Although the response by rice to cold stress has been described (Zhi-guo et al, 2014; Wang D. et al, 2016; Shakiba et al, 2017), we still need to identify more effective genes that can regulate this response.…”
Section: Introductionmentioning
confidence: 99%